2014
DOI: 10.1002/2013jb010932
|View full text |Cite
|
Sign up to set email alerts
|

Seismic noise correlations to image structural and mechanical changes associated with the Mw 7.9 2008 Wenchuan earthquake

Abstract: We locate temporal changes of seismic wave speed and scattering properties of the crust associated with the 2008 Mw7.9 Wenchuan earthquake. To that end, we analyze ambient seismic noise records from 2007 until the end of 2008 in the 1–3 s period band and in the 12–20 s period band measured in a region that covers the southern two thirds of the fault activated during the earthquake. To locate the changes, we use a refined imaging procedure based on the sensitivity of scattered waves to weak perturbations. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
112
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(120 citation statements)
references
References 35 publications
7
112
1
Order By: Relevance
“…Relaxation of the seismic velocity after perturbing rocks has been observed in laboratory studies (Ten Cate & Shankland 1996;Zaitsev et al 2003;Vakhnenko et al 2004;Ten Cate 2011) and field observations (Poupinet et al 1984;Schaff & Beroza 2004;Wegler & Sens-Schönfelder 2007;Brenguier et al 2008;Wu et al 2009;Nakata & Snieder 2011Wu & Peng 2012;Brenguier et al 2014;Obermann et al 2014;Richter et al 2014), and is thus an observable property under the right conditions. These observations usually show a recovery similar to the relaxation shown in Fig.…”
Section: R E L a X At I O N A S A D I A G N O S T I C O F C H A N G Ementioning
confidence: 89%
See 1 more Smart Citation
“…Relaxation of the seismic velocity after perturbing rocks has been observed in laboratory studies (Ten Cate & Shankland 1996;Zaitsev et al 2003;Vakhnenko et al 2004;Ten Cate 2011) and field observations (Poupinet et al 1984;Schaff & Beroza 2004;Wegler & Sens-Schönfelder 2007;Brenguier et al 2008;Wu et al 2009;Nakata & Snieder 2011Wu & Peng 2012;Brenguier et al 2014;Obermann et al 2014;Richter et al 2014), and is thus an observable property under the right conditions. These observations usually show a recovery similar to the relaxation shown in Fig.…”
Section: R E L a X At I O N A S A D I A G N O S T I C O F C H A N G Ementioning
confidence: 89%
“…Laboratory studies (Ten Cate & Shankland 1996;Zaitsev et al 2003;Vakhnenko et al 2004;Ten Cate 2011) and seismological field observations (Poupinet et al 1984;Schaff & Beroza 2004;Wegler & SensSchönfelder 2007;Brenguier et al 2008;Wu et al 2009;Nakata & Snieder 2011;Hobiger et al 2012;Nakata & Snieder 2012;Wu & Peng 2012;Brenguier et al 2014;Obermann et al 2014;Richter et al 2014;Gassenmeier et al 2016) show that the seismic velocity of rocks is often reduced during shaking, and recovers afterwards. Gassenmeier et al (2016) demonstrated that, at least in some cases, these changes are caused by the shaking of the subsurface that damages the material.…”
Section: Introductionmentioning
confidence: 99%
“…Seismic monitoring has been applied successfully on various scales (e.g. Obermann et al 2014;Salvermoser et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This may allow monitoring of subsurface velocity changes smaller than half a per cent and with a daily resolution (Sens-Schönfelder & Wegler 2006;Obermann et al 2014). Usually, the measurement of velocity changes relies on later arriving coda waves of ambientfield derived medium responses, which have followed an indirect and thus longer path through the medium.…”
Section: Introductionmentioning
confidence: 99%